2021
DOI: 10.1080/10408444.2021.1907530
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for measuring biofluid-based microRNA biomarkers

Abstract: MicroRNAs (miRNAs) are small non-coding RNA that regulate the expression of messenger RNA and are implicated in almost all cellular processes. Importantly, miRNAs can be released extracellularly and are stable in these matrices where they may serve as indicators of organ or cell-specific toxicity, disease, and biological status. There has thus been great enthusiasm for developing miRNAs as biomarkers of adverse outcomes for scientific, regulatory, and clinical purposes. Despite advances in measurement capabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 194 publications
(236 reference statements)
1
10
0
Order By: Relevance
“…However, once the sample is processed into serum or plasma, several studies have indicated that the miRNAs are stable from either fresh or frozen specimens. Even after several freeze-thaw cycles, minor to no alterations between fresh and frozen specimens were observed, which confirms that miRNAs are quite stable in circulation (Page et al, 2013b;Glinge et al, 2017;Chorley et al, 2021).…”
Section: Sample Processing and Storagesupporting
confidence: 56%
“…However, once the sample is processed into serum or plasma, several studies have indicated that the miRNAs are stable from either fresh or frozen specimens. Even after several freeze-thaw cycles, minor to no alterations between fresh and frozen specimens were observed, which confirms that miRNAs are quite stable in circulation (Page et al, 2013b;Glinge et al, 2017;Chorley et al, 2021).…”
Section: Sample Processing and Storagesupporting
confidence: 56%
“…Most epigenetic asthma studies have focused on miRNAs in blood and serum, and validation of their findings is needed to exclude spurious results due to differences in sample processing [136,137]. Despite this concern, many miRNAs have been consistently implicated in chronic respiratory or allergic diseases, highlighting their potential as possible therapeutic targets (e.g., miR-206 and miRNA-21) [101][102][103].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited consistent "housekeeping" miRNAs in human biofluids, and the heterogeneity of these samples makes the identification of one increasingly challenging. 96 Recently, Faraldi et al investigated the efficiency of 4 different normalization strategies for analyzing circulating miRNAs, including 1) the global mean of miRNA expression, 2) the mean of endogenous controls (33 stable miRNAs ranked by NormFinder 97 algorithm), 3) exogenous oligonucleotides (3 miRNAs), and 4) the single most stable endogenous miRNAs. 94 The investigators found that global, endogenous, and single-miRNA methods performed similarly in reducing the technical variability among their experimental replicates.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…105 There are various approaches for detecting dd-cfDNA; for instance, the use of preselected single nucleotide polymorphisms (SNPs) and high-throughput sequencing for readouts have been reported. [94][95][96] Currently, the two most common methods involve shotgun sequencing or droplet digital PCR (ddPCR). This data is expressed either as GcfDNA percentage (graft cfDNA/total cfDNA) or absolute quantification in copies/milliliter.…”
Section: Cell-free Dna As a Marker Of Graft Injurymentioning
confidence: 99%